Body composition versus body fat percentage as predictors of posture/balance control mobility and stability among football players under 21 years - Mohammed Zerf (Physical Education of Students)
Background: Overhead athletes require a delicate balance of shoulder mobility and stability in order to meet the functional demands of their respective sport. While musculoskeletal symptoms (LBP) [1] is one of warning against the consequences recorded in abnormal posture, bending, twisting, gardening and exercise levels among the sportsmen. Based on this theorem, the current study aims to determine the strong factor which affects mobility and stability among soccer players under 21 years. Material: 163 male players qualified from the Algerian football championship, engaged in the present study, selected by the intentional manner their average age 19,56±1.22 years. They were tested by saving tests (Body Fat Percentage (BFP) -Abdominal test (Abdo) - Modified Bass Test of Dynamic Balance (DB) and standing balance (SB)). As a statistical model, we chose regression analysis to predict the superiority of the variables chosen in the current study. Results: Based on the analysis statistics, we confirm: a) The high percentage of BFP is a great risk on the levels strengthens abdominal. b) The maintenance of stability (SB) depends on the additional BFP associated with the BMI ratio as being higher factors predicting the total amount of body weight related to the risks of instability. c) Maintaining dynamic mobility (DB) with respect to the displacement of the centre of gravity and its base support in the motion chain is based on excess body fat (BFP) in relation to body mass index (BMI) and Abdominal muscle strengthening levels (ABDO), as higher factors predicting the amount of weight gain. Conclusions: Founded on the variances acquired by the search, we highlight the relationship between body mass index (BMI) and body fat percent (BFP) as betters index predicting the influence of total amount body weight on mobility and stability among soccer players up to 21 years age. Evidence guide us to recommend, the evaluation of body composition as a part of body management and control. Where strong relationships between BMI and BFP suggests the anomalies postural, muscle coordination, movement control, balance and awareness of body position in both the tests.